At Westonci.ca, we provide reliable answers to your questions from a community of experts. Start exploring today! Explore our Q&A platform to find reliable answers from a wide range of experts in different fields. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
[tex]\left( \cfrac{1}{16} \right)^{3-2a}=64^{-a}\implies \left( \cfrac{1}{4^2} \right)^{3-2a}=(4^3)^{-a}\implies (4^{-2})^{3-2a}=4^{-3a} \\\\\\ (4^2)^{2a-3}=4^{-3a}\implies 4^{2(2a-3)}=4^{-3a}\implies 4^{4a-6}=4^{-3a} \\\\\\ 4a-6=-3a\implies -6=-7a\implies \cfrac{-6}{-7}=a\implies \cfrac{6}{7}=a[/tex]
We hope our answers were useful. Return anytime for more information and answers to any other questions you have. We hope this was helpful. Please come back whenever you need more information or answers to your queries. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.